Civil Liability for Omissions of Duties of Care Toward Older Persons in Chilean Law - Mendoza Alonzo, Pamela (2026)
This article examines the legal foundations of civil liability for omissions, within the framework of duties of care owed to older persons, with the aim of delineating the conditions under which inaction may constitute legally imputable conduct under article 2314 of the Chilean Civil Code. The central hypothesis advanced is that an omission gives rise to liability when the agent is bound to the victim by a special relationship that justifies the imposition of a positive duty to act, as is the case in contexts of family relationships, cohabitation or institutional protection. In such circumstances, the failure to act frustrates a legally relevant expectation of care, precludes the application of the principle of reliance and is normatively integrated as a form of unlawful conduct, a characterization that is particularly significant in relation to older persons in situations of dependency or vulnerability.The analysis is developed from a relational conception of the duty of care and makes auxiliary and circumscribed use of certain categories elaborated in criminal law doctrine—such as the position of guarantor—as tools for systematizing the duty to act in the civil law context, without implying a wholesale transposition of their underlying premises. It further advances the notion of an expectation of protection as the relational foundation of liabilityfor omissions, and substantiates the functional equivalence between acts and omissions in contexts involving the care of older persons.